Changing the System? : Artists talk about their practice : A Discussion Event in Rotterdam, April 1999. - Asdam, Knut; Bik, Liesbeth; Dragset, Ingar; Durham, Jimmie; Elmgreen, Michael; Eriksson, Annika; Esche, Charles; Green, Renée; Hosking, Mark; Jaukkuri, Maaretta; Kalkin, Adam; Kreuger, Anders; et al. (Helsinki : NIFCA - Nordic Institute for Contemporary Art, 1999)
Bik, Liesbeth ; Bismuth, Pierre ; Brown, Tony ; Cardiff, Janet ; Dragset, Ingar ; Durham, Jimmie ; Edefalk, Cecilia ; Elmgreen, Michael ; Eriksson, Annika ; Framis, Alicia ; Green, Renée ; Haaning, Jens ; Hausswolff, Carl Michael von ; Hosking, Mark ; Jonas, Joan ; Langenberg, Sjaak ; Leiderstam, Matts ; McBride, Rita ; Möller, Regina ; Nilsson, Lars ; van der Pol, Jos ; Ramberg, Lars ; Reyers, Zeger ; Roberts, Liisa ; Schmidt, Dierck ; Strik, Berend ; Thorsteinsson, Thorvaldor ; Tottie, Sophie ; Urbonas, Gediminas ; Valldosera, Eulàlia ; Walde, Martin ; Asdam, Knut
A Discussion Event in Rotterdam, April 1999.
Engels
boek